1992
DOI: 10.1128/aac.36.8.1596
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance to amikacin in a neonatal unit following intensive amikacin usage

Abstract: Gram-negative isolates from blood and cerebrospinal fluid were monitored for 1 year before and for 1 year after the first-line aminoglycoside in a busy pediatric department was changed from gentamicin to amikacin.In the general pediatric wards, the switch to amikacin resulted in no change in resistance of nosocomial gram-negative infections to either amikacin (0%Yo before and after) or gentamicin (23.9% [before] versus 26.5% [after]). In the neonatal unit, the switch to amikacin was followed by an outbreak of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In the present study the rate of amikacin resistance was found to be relatively high i.e. 35% however it may in accordance with Friedland et al who reported that amikacin resistance related to more intensive usage of amino glycosides (Friedland et al 1992). The increasing rate of amikacin in Pakistan was also reported by Akhtar N i.e.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study the rate of amikacin resistance was found to be relatively high i.e. 35% however it may in accordance with Friedland et al who reported that amikacin resistance related to more intensive usage of amino glycosides (Friedland et al 1992). The increasing rate of amikacin in Pakistan was also reported by Akhtar N i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Our model suggests the risk that this benefit would come at the cost of promoting high-level fluoroquinolone resistance; however, the properties of these agents to date seem to minimize such risk. Although resistance to newer fluoroquinolones has been reported (27), high-level resistance remains largely associated with previous treatment, and there has been only limited evidence of clonal spread of fluoroquinolone-resistant pneumococci (10)(11)(12)(13)28). These observations may imply a considerable fitness cost from acquiring incremental mutations associated with high-level fluoroquinolone resistance, a finding recently confirmed in animal models (28).…”
Section: Discussionmentioning
confidence: 58%
“…This result occurs when the delay leads to a large increase in Y 1 and when the new drug selects for Y 2 easily from this enlarged pool of Y 1 . Among the atypical scenarios (N ϭ 233), parameters involved in the acquired mechanism for resistance [i.e., e 12 , P, and Y 1 (0)] have means significantly higher than among the typical scenarios. Specifically, e 12 represents the likelihood of this selection and is shown to best differentiate an atypical scenario from a typical one (C-statistic ϭ 0.924).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations